PENGARUH FAKTOR BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGI TERHADAP KEPUTUSAN MEMBELI DI INDOMARET ( Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Katolik Santo Thomas Sumatera Utara ) - Tamba, Darwis (Jurnal Manajemen dan Bisnis, 2017)
The aim of this research, analyze the influence of cultural, social, personal and psychology of the buying decisions in Indomaret and analyzes of the four variables: cultural, social, personal and psychological variables which are the most dominant influence on buying decisions in Indomaret. Benefits study provides empirical evidence about the influence of cultural, social, personal and psychological on purchase decisions in Indomaret, provide knowledge to the public about cultural, social, personal and psychology of the buying decisions in Indomaret and contribute to the academic community about the importance of knowing the effect of factors cultural, social, personal and psychological on purchase decisions.The study population across the Faculty of Economics of the Catholic University of Santo Thomas North Sumatra ever shopped at Indomaret district of Medan Selayang while the study sample sebahagian the population can be considered representative. The total sample of 100 respondents, the type of data used primary and secondary data and data collection tools through questioner and documentation. Data analysis tool used regression.The results showed the multiple linear regression equation: KM = 3.503 + 0,122FBu 0,016FSo + + + 0,337FPsi 0,246FPri. The equation shows that cultural factors, social factors, individual factors, and psychological factors have a positive influence on the purchase decision will be positive. By F test, showing that the test results simultaneously (Test F) note the value F = 15.672 significance of 0.000 <0.05. It can be concluded jointly independent variable affecting kepusan Purchase. While the t test and the Individual Factors Psychological Factors positive and significant impact on KeputusanPembelian .This can be demonstrated by looking at the significance of each variable <0.05. As for the variable factors Cultural and Social Factors and no significant positive effect on the purchase decision. To facilitate the consumer if the consumer wants to buy branded items generally they will come to the big stores in the Mall. Party Indomaret should also be able to provide these things so Indomaret will be the goal of consumer spending and to facilitate consumer spending, the arrangement of items in Indomaret must tidy with lighting the lamp is bright and always pay attention to the items that have expired should be immediately withdrawn from the shelves dispalay.